Large−scale experimental investigations of specified granular fill materials for radon mitigation by active and passive soil depressurisations. (October 2019) - Hung, Le Chi; Goggins, Jamie; Croxford, Conor; Foley, Mark
Abstract: A series of large−scale experimental tests were performed to examine the flow behaviour of the T1 Struc and T2 Perm specified granular fill materials with active and passive depressurisations. Granular materials were compacted and tested at various compacted thicknesses. Compaction works were performed using a field compactor and compaction degrees of the materials were found to be higher than those induced by a standardised small-scale compactor. The air permeability ( k ah ) values of the materials were obtained with active depressurisation. It was found that the overall trend of k ah tended to decrease with the increase in the compacted thickness of the materials and were found to be compatible with those determined by the small-scale test apparatus. Results from passive depressurisation tests indicated that the rotating cowls performed the best, followed by a static open pipe and a pipe with a cap. Highlights: Flow behaviors of granular materials were experimentally examined. Flow behaviors of granular materials are critical for soil depressurisation systems. Field compaction of granular materials is higher than the laboratory compaction. Compacted thickness of a granular material strongly affects its air permeability. Scale effect should be considered when examining the flow behaviour of granular materials.